The Stress Distribution on the Zygapophyseal Joint of Lumbar Vertebra by ANSYS Program - Jaffar, Akram A.; Abass, Sadiq J.; M. Mukhtar, Summer S. (Al-Khwarizmi Engineering Journal, 2010)
Zygapophyseal joints (or facet joints), are a plane synovial joint which located between the articular facet processes of the vertebral arch which is freely guided movable joints. Ten dried vertebrae were used for the lumbar region and taking (L4) as a sample to reveal stress pathways across the joints by using ANSYS program under different loading conditions which used Finite Elements Analysis model. Results obtained from the ANSYS program are important in understanding the boundary conditions for load analysis and the points of stress concentration which explained from the anatomical point of view and linked to muscle and ligament attachments. This model used as a computational tool to joint biomechanics and to prosthetic implant analysis.